2009
DOI: 10.1007/s11282-009-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between panoramic radiomorphometric indices and the femoral bone mineral density of edentulous patients

Abstract: Objectives To determine the relative efficacy of panoramic radiomorphometric indices in detecting osteoporosis, and optimal thresholds for referral for osteoporosis investigation in edentulous patients. Methods Forty-nine edentulous patients, age 41-78 years, were divided into normal and osteopenic/osteoporotic groups according to femoral bone mineral density. Panoramic radiographs were obtained to determine the mandibular cortical index (C1, normal; C2, mild; and C3, severe erosion of mandibular cortex), ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“…This result almost in line with two previous studies, but these results show a discrepancy with previous studies (Gulsahi et al, 2009;Ledgerton et al, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…This result almost in line with two previous studies, but these results show a discrepancy with previous studies (Gulsahi et al, 2009;Ledgerton et al, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…(3) CT mandibular index (CTI) symbolized the panoramic mandibular index (PMI), which represented the ratio of the thickness of the mandibular cortex to the distance between the middle of the mental foramen and the inferior mandibular cortex. 11 This was measured on the non-orthogonal coronal image obtained after slice preparation (Figure 3). The measurement was made on both sides and the mean value was used in statistical analysis.…”
Section: Slice Selectionmentioning
confidence: 99%
“…The efficiency of these indices had shown a debate: while some investigations consider them effective in diagnosing osteoporosis, 8,9 others reported that some of these indices are not. [10][11][12] Fractal dimension (FD) analysis is a statistical texture analysis that is based on fractal mathematics for describing complex shapes and structural patterns. It is used to express the texture roughness and indicate figure complexity by characterizing self-similarity of the texture grey-level variations over different scales.…”
Section: Introductionmentioning
confidence: 99%
“…No suitable machines are available in Laos. A number of studies have indicated that a dental panoramic radiograph may be a suitable tool to measure bone mineral densities [12][13][14][15][16][17][18][19][20]24,25) . In this study digital panoramic radiographic equipment was used to obtain the images.…”
Section: Discussionmentioning
confidence: 99%
“…Images were exported as DICOM image stacks to the Department of Oral and Maxillofacial Radiology, Nihon University School of Dentistry, by a telemedicine system with functions for image viewing, image transfer, DICOM storage real-time video conferencing, and 24 MCW has been shown to be a good measure of bone mass in the mandible compared with the other indices [12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Sisounthone et al 21) have reported that the overall average MCW of 519 Laotian patients aged 7-79 years was lower than that observed in Europeans.…”
Section: Subjectsmentioning
confidence: 99%